Morphological and anatomical characterization of bleached soda, soda-AQ and kraft pulps from essential oil isolated citronella grass. (2020) - Sharma, Nidhi; Bhawana; Godiyal, R.D.; Thapliyal, B.P.; Anupam, Kumar
Abstract: Morphology and anatomy of pulp fibres are very crucial in determining the physical and strength properties of paper sheets prepared from them. This study reports the morphological and anatomical features of bleached soda, soda-AQ (Soda-anthraquinone) and kraft pulp fibres obtained from solid residues left after extraction of essential oil from Citronella grass ( Cymbopogon winterianus Jowitt) using hydro-distillation. Their surface morphology and structural properties were also analyzed using SEM (Scanning electron microscope) and FTIR (Fourier transform infrared) spectroscope. The pulps exhibited mean length-weighted length ∼709–736 µm, average fibre width ∼13.5–14.4 µm, average fibre curl ̴ 8%, average fines length ∼49–51 µm and average fines area ∼1001–1058 µm. The parenchyma length, parenchyma width, vessels length, vessels width, lumen diameter and cell wall thickness of the bleached soda–AQ pulp were found to be 205.92 µm, 96.62 µm, 515.84 µm, 35.28 µm, 4.45 µm and 4.53 µm respectively. SEM analysis of paper hand sheets revealed a dense network of well bounded fibres within the matrix while FTIR analysis demonstrated presence of characteristic bands of cellulose, lignin and hemicellulose in pulp samples. Comparison of morphological and anatomical features of these pulps with those of other grasses and non-woody raw materials confirmed the suitability of essential oil isolated Citronella grass as potential raw material for pulp and paper industry.